Searching for Function: Reconstructing Adaptive Niche Changes Using Geochemical and Morphological Data in Planktonic Foraminifera - Kearns, Lorna E.; Bohaty, Steven M.; Edgar, K. M.; Nogué, Sandra; Ezard, Thomas H. G. (Frontiers in Ecology and Evolution, 2021)
Dead species remain dead. The diversity record of life is littered with examples of diversity declines and radiations, yet no species has ever re-evolved following its true extinction. In contrast, functional traits can transcend diversity declines, often develop iteratively and are taxon-free allowing application across taxa, environments and time. Planktonic foraminifera have an unrivalled, near continuous fossil record for the past 200 million years making them a perfect test organism to understand trait changes through time, but the functional role of morphology in determining habitat occupation has been questioned. Here, we use single specimen stable isotopes to reconstruct the water depth habitat of individual planktonic foraminifera in the genus Subbotina alongside morphological measurements of the tests to understand trait changes through the Middle Eocene Climatic Optimum (MECO: ~40 Myr ago (mega annum, Ma)). The MECO is a geologically transient global warming interval that marks the beginning of widespread biotic reorganizations in marine organisms spanning a size spectrum from diatoms to whales. In contrast to other planktonic foraminiferal genera, the subbotinids flourished through this interval despite multiple climatic perturbations superimposed on a changing background climate. Through coupled trait and geochemical analysis, we show that Subbotina survival through this climatically dynamic interval was aided by trait plasticity and a wider ecological niche than previously thought for a subthermocline dwelling genus supporting a generalist life strategy. We also show how individually resolved oxygen isotopes can track shifts in depth occupancy through climatic upheaval. During and following the MECO, temperature changes were substantial in the thermocline and subthermocline in comparison to the muted responses of the surface ocean. In our post-MECO samples, we observe restoration of planktonic foraminifera depth stratification. Despite these changing temperatures and occupied depths, we do not detect a contemporaneous morphological response implying that readily available traits such as test size and shape do not have a clear functional role in this generalist genus. Modern imaging measurement technologies offer a promising route to gather more informative morphological traits for functional analysis, rather than the traditional candidates that are most easily measured.